IRE1α promotes cell apoptosis and an inflammatory response in endoplasmic reticulum stress-induced rheumatoid arthritis fibroblast-like synovial cells by enhancing autophagy - Yang, Jialiang; Ma, Zhenzhen; Jia, Qian; Li, Yanshan; Lu, Yucheng; Yang, Qingrui (Penerbit Universiti Kebangsaan Malaysia, 2022)
Endoplasmic reticulum (ER) stress can induce autophagy via the unfolded protein response (UPR), and autophagy can regulate the activation of inflammasomes. Inositol-requiring enzyme 1α (IRE1α) is a transducer of the UPR in cells with ER stress. Here, we investigated the role of IRE1α and its impact on ER stress in rheumatoid arthritis fibroblast-like synovial cells (RA-FLSs). RA-FLSs were isolated from rheumatoid arthritis (RA) patients and stimulated with thapsigargin (TG) to produce ER stress cells. ER stress-, autophagy and the expression of apoptosis-associated factors were investigated by western blotting and the qRT-PCR. Cellular ROS levels were assessed by flow cytometry. ELISAs were performed to determine the concentrations of inflammatory mediators. TG treatment promoted IRE1α, GRP78, CHOP, and ATP6 mRNA and protein expression. ROS generation was increased in TG-induced RA-FLSs; additionally, TG was found to induce cell inflammation by upregulating the expression of inflammasome markers and the concentrations of inflammatory mediators. The levels of autophagy markers, apoptosis-associated proteins, and mRNA were increased in TG-stimulated RA-FLSs. However, transfection with si-IRE1α suppressed TG-induced increases in ROS generation, inflammation levels, cell apoptosis, and autophagy in RA-FLSs. Treatment with the autophagy activator RAPA attenuated the protective effects of IRE1α silencing on TG-induced RA-FLS apoptosis and inflammatory damage. Our findings showed that in RA-FLSs, IRE1α silencing alleviated ER stress-induced inflammation and apoptosis caused by autophagy.